RUSSIA’S POLITICS IN THE NORTHERN CAUCASUS: YSTEMIC CRISIS AND HOW TO OVERCOME IT - MARKEDONOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2006)
Today, the social and political situation in the Russian Northern Caucasus is becoming increasingly unstable. It is no longer the problem of a gradually rising number of terrorist and other extremist acts and radical political initiatives—it is a widespread systemic crisis of Russia’s North Caucasian policy and its key elements (administration, appointments, and ideology). In the absence of anti-crisis measures, the continuing crisis trends are fraught with unpredictable results. It would be methodologically wrong, though, to look at the region as the “breeding soil” of terrorism and extremism. The North Caucasian situation not only reflects the problems of Russia’s domestic policies and its “ailments”—it makes them even worse. The re-division of property is accompanied by assassination of the losers; the power struggle goes hand in hand with ethnic and religious conflicts; and the privatization of power is tinged with clan and tribal hues In 2005, several local ethnic conflicts (believed to be frozen since the mid-1990s) were reloaded. The Battle of Borozdinovskaia, in the course of which the Iamadaev brothers “mopped up” a village populated by ethnic Daghestanis, worsened the already bad relations between the Chechens and Daghestanis. The imminent reform of local self-administration caused another upsurge of ethnic tension between the Ossets and Ingushes in the Prigorodniy District, since one of the conflicting sides (the Ingushes) was convinced that its ethnic interests were endangered. The contested Prigorodniy District claimed by North Ossetia and Ingushetia united the anti-Ziazikov (read: anti-Kremlin) opposition in Ingushetia. In 2005, it tried to launch a regional “color revolution” in Nazran, but this attempt failed. The far from friendly relations between the Ossets and Ingushes caused another round of the “arms race” in the Caucasus. In September 2005, Minister of Internal Affairs of North Ossetia Sergey Arenin suggested that civilians should be armed and united into groups to protect themselves and, as the minister put it, “people’s squads” armed with hunting rifles would exercise public control over the law enforcement bodies; they were also expected to help prevent ethnic conflicts. The neighbors did not like it: Musa Apiev, Deputy Minister of Internal Affairs of Ingushetia, dismissed the idea as “doubtful” and said quite rightly that the civilians should be disarmed rather than en couraged to take up weapons. At the same time, Kazbek Sultygov, chairman of the Republican Committee for Refugees, wrote to President Putin suggesting that direct federal rule be introduced in the Prigorodniy District; by way of explanation he added that the Osset leaders were turning a blind eye to the mass illegal actions against the Ingushes. The North Ossetia leaders, in turn, submitted a report about the crimes committed by ethnic Ingushes in their republic. The Center preferred to let the events take their own course. It was not the Center’s firm and principled position that softened the North Ossetian minister’s initiative. Today, the Chermen checkpoint on the administrative border between North Ossetia and Ingushetia looks more like a fortress on a state border. However, the leaders of the single country to which both republics belong are painstakingly avoiding any political and legal assessments of the armed conflict between the Ossets and Ingushes which dates back to October 1992.